How does an adaptation of forest management to storm damage risk affect indicators for sustainable forestry? - Larsson, Linnea (2022)
With a changing climate, the risk for damage to the forest will increase. In Sweden, large storm damages have been more common under the 20th century and are also the damaging event that has resulted in the largest damages in Europe. The aim of the thesis is to investigate how various indicators for sustainable forestry and forest management are affected if the management objective is to minimize the risk for storm damages 100 years in future. Data from the national forest inventory was used in the decision support system Heureka PlanWise for a trade-off analysis between the risk for storm damage and indicators representing forest economy, production, nature conservation, biodiversity, carbon storage and recreation. The study areas were Lycksele municipality and Växjö municipality. All indicator values were reduced when the storm damage risk was minimized, for both Lycksele and Växjö municipalities. Higher standing volume, age and height, and active thinning management were some of the forest characteristics that increased storm damage risk. The optimal combination of management strategies when minimizing storm damage risk included most management without thinnings, which was relatively uncommon when managing the forest for other objectives. There are possibilities to adapt forest planning and forest management to reduce the risk for storm damage, especially when considering forest management objectives such as high net revenue, harvested volume, and growth.